Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2023
DOI: 10.1007/s12652-023-04530-y
|View full text |Cite
|
Sign up to set email alerts
|

Machine learning in crime prediction

Abstract: Predicting crimes before they occur can save lives and losses of property. With the help of machine learning, many researchers have studied predicting crimes extensively. In this paper, we evaluate state-of-the-art crime prediction techniques that are available in the last decade, discuss possible challenges, and provide a discussion about the future work that could be conducted in the field of crime prediction. Although many works aim to predict crimes, the datasets they used and methods that are applied are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(10 citation statements)
references
References 81 publications
0
1
0
Order By: Relevance
“…Precision is the ratio of true positives (TP) to the sum of true positives (TP) and false positives (FP), recall is the ratio of true positives (TP) to the sum of true positives (TP) and false negatives (FN), and the F1-score is the harmonic mean of precision and recall. Accuracy refers to the percentage of correct predictions [5,13]. As is shown in Table 7, the oversampled random forest model utilized in this study exhibits a superior performance.…”
Section: Crime Prediction Resultsmentioning
confidence: 92%
See 2 more Smart Citations
“…Precision is the ratio of true positives (TP) to the sum of true positives (TP) and false positives (FP), recall is the ratio of true positives (TP) to the sum of true positives (TP) and false negatives (FN), and the F1-score is the harmonic mean of precision and recall. Accuracy refers to the percentage of correct predictions [5,13]. As is shown in Table 7, the oversampled random forest model utilized in this study exhibits a superior performance.…”
Section: Crime Prediction Resultsmentioning
confidence: 92%
“…According to the prediction process shown in Figure 7, crime events were forecasted. The prediction models are evaluated using metrics such as the accuracy, precision, recall, and F1-score, and were compared with algorithms including logistic regression, decision trees, Bayesian methods, random forests, and KNN [5][6][7]. Precision is the ratio of true positives (TP) to the sum of true positives (TP) and false positives (FP), recall is the ratio of true positives (TP) to the sum of true positives (TP) and false negatives (FN), and the F1-score is the harmonic mean of precision and recall.…”
Section: Crime Prediction Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Besides solving the number of cases being lodged day by day, it is essential to prevent crime that may happen in the future. [11] For this it is essential to analysis crime and carry out a detailed inspection of ongoing crime. In this paper, analysis of vast amount of data is done and meaningful results using machine learning algorithms has been derived.…”
Section: Introductionmentioning
confidence: 99%
“…The study concluded that supervised learning approaches were used more frequently in crime prediction studies, and Logistic Regression is the most powerful method for predicting crime. Another paper (Jenga et al, 2023) evaluated crime prediction techniques using machine learning and discussed the challenges and future work in this field. The researchers used a Systematic Literature Review (SLR) methodology to collect and synthesize the required knowledge, and formulated eight research questions, highlighting that most of the papers used a supervised machine learning approach.…”
Section: Introductionmentioning
confidence: 99%